Heteroatom-Doped Porous Carbon-Based Nanostructures for Electrochemical CO2 Reduction - Qingqing Lu; Kamel Eid; Wenpeng Li (Nanomaterials, 2022)
The continual rise of the CO2 concentration in the Earth’s atmosphere is the foremost reason for environmental concerns such as global warming, ocean acidification, rising sea levels, and the extinction of various species. The electrochemical CO2 reduction (CO2RR) is a promising green and efficient approach for converting CO2 to high-value-added products such as alcohols, acids, and chemicals. Developing efficient and low-cost electrocatalysts is the main barrier to scaling up CO2RR for large-scale applications. Heteroatom-doped porous carbon-based (HA-PCs) catalysts are deemed as green, efficient, low-cost, and durable electrocatalysts for the CO2RR due to their great physiochemical and catalytic merits (i.e., great surface area, electrical conductivity, rich electrical density, active sites, inferior H2 evolution activity, tailorable structures, and chemical–physical–thermal stability). They are also easily synthesized in a high yield from inexpensive and earth-abundant resources that meet sustainability and large-scale requirements. This review emphasizes the rational synthesis of HA-PCs for the CO2RR rooting from the engineering methods of HA-PCs to the effect of mono, binary, and ternary dopants (i.e., N, S, F, or B) on the CO2RR activity and durability. The effect of CO2 on the environment and human health, in addition to the recent advances in CO2RR fundamental pathways and mechanisms, are also discussed. Finally, the evolving challenges and future perspectives on the development of heteroatom-doped porous carbon-based nanocatalysts for the CO2RR are underlined.